Estimating the extent and nature of offending by Sudanese-born individuals in Victoria - Shepherd, Stephane M. (The Australian and New Zealand journal of criminology, 2020)
The involvement in crime of some young Sudanese-born Victorians has received sustained public attention in recent years. The media coverage of these occurrences has been extensive, with some outlets criticised for sensationalist reporting and prejudiced undertones. A range of views were held across the commentariat including, for example, the notion that Sudanese-Victorian criminal involvement has been overstated; that some level of justice over-representation was inevitable due to the demographics of Sudanese-born Victorians, which skew young and male (i.e. the demographic hypothesis); and that offending rates may be associated with heightened law enforcement responses following a high-profile criminal incident in March 2016 that received protracted media coverage and political commentary (i.e. the racial-profiling hypothesis). This paper sought to address these contentions by (i) examining the offending rates of both young and adult males across three cultural sub-groups (i.e. Sudanese-born, Indigenous Australian, Australian-born) across several offending categories between 2015 and 2018 and (ii) exploring the impact of a high-profile criminal incident in March 2016, on the offending rates of Sudanese-born Victorians. Offending rates were calculated using offender incident data from the Victorian Crime Statistics Agency and population estimates from the Australian Bureau of Statistics Census data. Findings indicate that Sudanese-born individuals figure prominently in both youth and adult offending categories relative to other major cultural sub-groups. Rates for ‘crimes against the person’ were especially pronounced for Sudanese-born youth and significantly higher than rates for crimes more subject to police discretion (i.e. public order offences). The ‘demographic hypothesis’ did not hold for the specified age range of 10 to 17 years. An increase in offending was observed post-March 2016 across two offending categories for Sudanese-born Victorians. Findings are contextualised within.